Crystal structure of Thermoanaerobacter tengcongensis hypoxanthine‐guanine phosphoribosyl transferase L160I mutant − insights into inhibitor design - Chen, Qiang; You, Delin; Liang, Yuhe; Su, Xiaodong; Gu, Xiaocheng; Luo, Ming; Zheng, Xiaofeng (The FEBS journal, 2007)
Hypoxanthine‐guanine phosphoribosyltransferase (HGPRT) is a potential target for structure‐based inhibitor design for the treatment of parasitic diseases. We created point mutants of Thermoanaerobacter tengcongensis HGPRT and tested their activities to identify side chains that were important for function. Mutating residues Leu160 and Lys133 substantially diminished the activity of HGPRT, confirming their importance in catalysis. All 11 HGPRT mutants were subject to crystallization screening. The crystal structure of one mutant, L160I, was determined at 1.7 Å resolution. Surprisingly, the active site is occupied by a peptide from the N‐terminus of a neighboring tetramer. These crystal contacts suggest an alternate strategy for structure‐based inhibitor design.